Photocatalytic Activity and Antibacterial Behavior of Polyaniline-Doped Titanium Oxide Layers. (2022) - Ali, Aya; Janorkar, A; Marquart, M; Griggs, J; Bumgardner, J.; Roach, M
Abstract : Purpose/Aim: The purpose of this study was to evaluate the effect of polyaniline doping of mixed anatase and rutile phase titanium oxide layers on the resulting photocatalytic activity (PCA) and antibacterial behavior. Materials and Methods: Commercially pure titanium grade 4 (CPTi) samples were divided into three groups: (1) anodized in 0.5 M sulfuric acid (control); (2) electropolymerized using cyclic voltammetry in a mixture of 0.5 M sulfuric acid and 0.25 M aniline after anodization in 0.5 M sulfuric acid (ACV); and (3) anodized in 0.5 M sulfuric acid and 0.25 M aniline (AAn). SEM, XRD, and water contact angles were used to evaluate the surface morphology, oxide layer crystallinity, and hydrophilicity of the oxide layers (n= 3). The PCA was determined through methylene blue (MB) degradation assay using 365 nm UVA illumination (n= 7). The antibacterial behavior was evaluated by assessing the reduction in percentage of S.aureus attachment under three UVA lighting conditions: (1) a pre-illumination group in which samples were irradiated under UVA light for one hour prior to bacteria exposure; (2) direct illumination group in which samples were irradiated for one hour after bacteria exposure; and (3) a no illumination group in which the samples were kept in the dark for one hour after bacteria exposure (n= 5). Results: SEM confirmed the presence of polyaniline on AAN and ACV group surfaces. XRD confirmed the presence of anatase and rutile peaks for all groups with lower peak intensities for the AAn group. AAn, with an average contact angle of 29.7°, showed significantly higher hydrophilicity (p= 0.041) compared to the ACV and control groups with average contact angles of 46.4° and 47.9°, respectively. AAn showed significantly higher MB degradation at 60 minutes when compared to ACV (p= 0.034). Bacterial testing showed no significance differences between the three groups. However, an increased trend of bacterial attachment reduction was shown for the AAn and ACV groups, averaging 90.7% and 87.7%, compared to the control group, averaging 72.7%, under direct UVA illumination. Conclusions: Doping of polyaniline into the titanium oxide layer by direct anodization in sulfuric acid and aniline improves the hydrophilicity and photocatalytic activity of the titanium surfaces. Although polyaniline doped titanium oxide showed promising trends, no significant differences were shown in the antibacterial behaviors of the surfaces that were tested in this study. Additional studies using different concentration of aniline in the anodizing electrolyte are needed to attempt to improve photocatalytic activity and reduce bacterial attachment.